2021
DOI: 10.3390/cancers13030477
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Targeting IL-1 in Cancer

Abstract: Since its discovery, interleukin-1 has been extensively studied in a wide range of medical fields. Besides carrying out vital physiological functions, it has been implicated with a pivotal role in the progression and spreading of different cancer entities. During the last years, several clinical trials have been conducted, shedding light on the role of IL-1 blocking agents for the treatment of cancer. Additionally, recent developments in the field of immuno-oncology have implicated IL-1-induced signaling casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 104 publications
0
33
0
Order By: Relevance
“…39 Anti-IL1B mAb canakinumab has been now clinically evaluated in combination with immunotherapy or chemotherapy for treating various types of cancers, including lung cancer, pancreatic cancer, and renal cancer. 40 Usually, anti-PD1 mAb is the first choice as an immunotherapeutic in combination with other drugs despite many failures in the clinical trials. 16 However, blocking PD1 is likely helpless in the treatment of metastatic CRC, since almost no differences of PD1 + T cells in PBMCs were observed between healthy donors and patients with CRC (figure 5A), and blocking PD1 may be ineffective in suppressing tumor promotion via the TAMy-caused lipidization.…”
Section: Discussionmentioning
confidence: 99%
“…39 Anti-IL1B mAb canakinumab has been now clinically evaluated in combination with immunotherapy or chemotherapy for treating various types of cancers, including lung cancer, pancreatic cancer, and renal cancer. 40 Usually, anti-PD1 mAb is the first choice as an immunotherapeutic in combination with other drugs despite many failures in the clinical trials. 16 However, blocking PD1 is likely helpless in the treatment of metastatic CRC, since almost no differences of PD1 + T cells in PBMCs were observed between healthy donors and patients with CRC (figure 5A), and blocking PD1 may be ineffective in suppressing tumor promotion via the TAMy-caused lipidization.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1, for example, is a downstream effector of Ras activation and NF-ÎșB regulatory gene activation, which is necessary to provide a favorable microenvironment for tumor formation [ 105 ]. A recent second phase of a clinical trial of a recombinant IL-1R antagonist for multiple myeloma has shown a favorable safety profile and reduced morbidity, demonstrating that anti-IL-1 therapy is a viable cancer treatment option [ 106 ]. BBR inhibits the inflammatory cytokine caspase-1 activation through ERK1/2 signaling as well as glioma cells’ subsequent development of IL-1 and IL-18.…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Inflammation also plays a role in the development and progression of cancer ( 30 , 31 ). IL-1 has been shown to mediate tumor angiogenesis, metastasis, and tumor immune evasion ( 32 , 33 ). IL-1 initiates and amplifies inflammation and can be produced by both immune (myeloid cells, macrophages, etc) and nonimmune cells in response to danger-associated molecular patterns and pathogen-associated molecular patterns ( 34 ).…”
Section: An Inflammatory Common Link Among Atherosclerosis Af and Cancermentioning
confidence: 99%